FeCoNi Sulfides Derived From In situ Sulfurization of Precursor Oxides as Oxygen Evolution Reaction Catalyst - Teng, Wanqing; Huo, Mengtian; Sun, Zhaomei; Yang, Wenrong; Zheng, Xiangjiang; Ding, Caifeng; Zhang, Shusheng (Frontiers in Chemistry, 2020)
It is highly promising to design and develop efficient and economical electrocatalysts for oxygen evolution reaction (OER) in alkaline solution. In this work, we prepare FeCoNi sulfides composites (including FeS, Co3S4 and Ni3S4) derived from in-situ sulfurization of precursor oxides on carbon cloth, which are used to be oxygen evolution reaction (OER) catalyst. Such catalyst shows excellent OER performance, low overpotential, small Tafel slope, high electrochemical stability, and it is a promising electrocatalyst for OER in alkaline media.